SERVICE QUALITY ACCEPTANCE ON LOW COST CARRIER - Reza Soraya; Dary Wira Mahadika; Dewi Tamara; Gerry Rizki Sanjaya (Jurnal TAM (Technology Acceptance Model), 2023)
Perceived service quality is the foundation for comprehending transportation needs, as it influences consumers' selection of the numerous types of services that are continuously evolving. A company's success is determined by its ability to please its clients. This study's objective is to examine the influence of Electronic Word of Mouth (E-WOM) and Perceived Service Quality from Low-Cost Carrier on Brand Image, Customer Satisfaction, and Loyalty. Explanatory research employing a quantitative methodology will be used by the author for this study. This study used a non-probability sampling strategy with a purposive sampling method, meaning the selection of samples is not random but rather based on specified criteria, notably prior experience with LCC (Low-Cost Carrier) or low-cost airlines. Using an adapted SERVQUAL scale, 249 participants who were domestic travelers from Indonesia were contacted.  SmartPLS 3 utilized Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate the research data. Perceived service quality was a significant predictor of customer satisfaction (β = 0.877, p = 0.000), corporate image (β = 0.607, p = 0.000), and customer loyalty (β = 0.456, p = 0.000), as indicated by the results. EWOM will increase consumer loyalty to low-cost carriers (β = 0.182, p = 0.028). On the basis of these results, LCCs should develop future strategic plans that significantly emphasize the enhancement of service quality metrics